2022
DOI: 10.1002/qj.4322
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic and non‐linear representation of model uncertainty in a convective‐scale ensemble prediction system

Abstract: Accurately addressing model uncertainties with a consideration of the enhanced effect of non-linearities in a high-resolution convective-scale system is a crucial issue for performing convection-allowing ensemble prediction systems (CAEPSs). In this study, a conditional non-linear-stochastic perturbation method is developed to simultaneously consider both a stochastic and a non-linear representation of model uncertainties associated with physics parameterization in the Global and Regional Assimilation and Pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…For instance, Xu et al . (2022a, 2022b) superimposed the first NFSV on SPPT perturbations and further improved the probabilistic skill of convective‐scale systems. In fact, when comparing the O‐NFSVs with SKEB and SPPT, we found that with the change in model resolution, they differentially impact the TC forecasting skill.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For instance, Xu et al . (2022a, 2022b) superimposed the first NFSV on SPPT perturbations and further improved the probabilistic skill of convective‐scale systems. In fact, when comparing the O‐NFSVs with SKEB and SPPT, we found that with the change in model resolution, they differentially impact the TC forecasting skill.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Multiple perturbation schemes are often adopted to achieve higher forecasting skill (Jankov, 2017;Melhauser et al, 2017;Xu et al, 2022aXu et al, , 2022b. For instance, Xu et al (2022aXu et al ( , 2022b superimposed the first NFSV on SPPT perturbations and further improved the probabilistic skill of convective-scale systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations